Influence of droplet size and azoxystrobin insensitivity on frogeye leaf spot management in soybean. (October 2018) - Butler, Shawn; Kelly, Heather; Mueller, Thomas; Kruger, Greg; Cochran, Alicia; Raper, Tyson
Abstract: Field experiments were conducted in 2014 and 2015 to evaluate the influence of droplet size on foliar fungicide efficacy and leaf residue in soybean infected with Cercospora sojina, the fungal agent of frogeye leaf spot. A fungicide premix of azoxystrobin and difenoconazole was applied using two spray nozzles with varying droplet spectra. No significant differences were found among treatments in regards to visual disease ratings, soybean yield, and azoxystrobin leaf residue at 0, 2, 7, and 14 days after application. Results suggest that the potential reduction in coverage from drift-reduction nozzle technology may not negatively affect the efficacy of a tank mix of azoxystrobin and difenoconazole on frogeye leaf spot in soybean. Highlights: Drift-reduction nozzles are now required on herbicide labels for new tolerant crop varieties. Impact of drift-reduction nozzles were previously considered to negatively affect foliar fungicide applications. Frogeye leaf spot, resistant to strobilurin fungicides, is harmful to soybean yields. Drift-reduction nozzles can be an efficacious alternative in comparison to conventional spray nozzles previously recommended.